Supportive Dyadic Coping sebagai Moderator dalam Peran Parental Stress terhadap Kepuasan Pernikahan dalam Transisi Menjadi Orang Tua - Maharini, Mutiara; Ginanjar, Adriana Soekandar (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The transition to parenthood has proven to be challenging and stressful for most couples. The COVID-19 pandemic has created even more hardships, creating the potential for increased parental stress and can significantly reduce marital satisfaction. It is known that parents' coping methods can affect the level of perceived stress and marital satisfaction. This study aims to examine the buffering effect of supportive dyadic coping in reducing the impact of parental stress on marital satisfaction in the transition to becoming new parents. To test the hypothesis, we conducted a study using the Parental Stress Scale (PSS), Dyadic Coping Inventory (DCI), and Couple Satisfaction Index (CSI). In Indonesia, we collected data from 112 new parents (N mothers = 90%, M age = 27.9, SD age = 2.8). The dimension of emotion-focused supportive DC was found to be significant in moderating the role of parental stress on marital satisfaction F(1, 111) = 11.21, p<0.005. In contrast, problem-focused supportive dyadic coping F(1, 111) = 26.39, p> .005 was found not to be significant in reducing the impact of parental stress on marital satisfaction. The researcher found that parental stress F(1.112) = -2.964, p<.05, significantly predicts marital satisfaction regardless of the level of supportive dyadic coping. In addition, we found that there was a direct effect of emotion-focused supportive dyadic coping on marital satisfaction with a value of β = 6.04, 95% BCa CI [2.52, 9.55], p<0.01 and a direct effect of problem-focused supportive dyadic coping with β = 6.24, 95% BCa CI [1.81, 10.66], p<0.05. The results show that in the transition to parenthood, couples must consider the importance of supportive dyadic coping to maintain marital satisfaction.